Collection of data for children of 0 - 5 years: construction and validation of an instrument - Kenya Lima Silva; Maria Miriam Lima da Nóbrega (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Study of the methodological type that had as objective to construct and to validate of an instrument of collection of data for children of 0 the 5 years taken care of in the Pediatrics Clinic of the University Hospital Lauro Wanderley and to test the operacionalition of the instrument with children of the Pediatrics Clinic. The same it was I base in the Theory of the Needs Basic Human of Horta. For the construction of the instrument, it was used specialized literature of the area of pediatrics nursing and pediatrics, for the identification of the manifestations of the needs basic human more frequent in the children of this years band, these had been submitted to the content validation, to nurses of the area, being used in the construction of the instrument alone the manifestations that had presented weighed mean >0.80. In the choice of the format and structure of the instrument, opted if for keeping in the standardized format for the previous Hospital, identification; previous internments/main complaints; human needs basic/physical exam; and the nurse impressions keeping following sequence of the validated needs: oxygenation needs, of nutrition, hydratation and hydrica and electrolytic regulation, needs of elimination, sleep and rest, exercise and physical activity, corporal mechanics, motility, corporal care, physical integrity and mucous cutaneo, needs of thermal, hormonal regulation, neurology, immunology, cellular growth and needs of locomotion, needs of vascular regulation and needs of perception, security, love and acceptance and gregary, needs of communication, leisure and recreation.